Analisis Pengaruh Kompensasi, Kerjasama Tim dan Budaya Organisasi terhadap Kepuasan Kerja serta Dampaknya pada Kinerja Karyawan PT. Bank Muamalat Cabang Banda Aceh - Syarifah Mauli Masyithah; M Adam; Mirza Tabrani (SI-MEN, 2018)
This study aims to determine the effect of compensation, teamwork, and organizational culture on job satisfaction and its impact on the performance of employees of Bank Muamalat Branch of Banda Aceh. The study included all employees of Bank Muamalat Branch of Banda Aceh totaling 119 respondents. The data analysis method used is Partial Least Square (PLS) with 5.0 WarpPLS program. The results showed that compensation, teamwork, organizational culture, and job satisfaction have partial and significant effect on the performance of employees with the highest coefficient value contained in job satisfaction is 0.76. Then compensation, teamwork, and organizational culture have partial effect on job satisfaction while organizational culture variable gain highest coefficient of 0.74. The test results show that the model of the indirect effect of job satisfaction partially mediates the relationship between each of the independent variables on the performance of employees. The test model of direct effect to simultaneously show there is influence of variable compensation, teamwork, and organizational culture on employee performance and job satisfaction. And the full model test results show that compensation, teamwork, and organizational culture has silmultan effect on job satisfaction and impact on employee performance. The effect of compensation and organizational culture on employee performance remained significant with a coefficient respectively 0.15 and 0.18. While the influence of teamwork on performance is insignificant and the coefficient of p = 0.27. The influence of job satisfaction on the significant performance with a coefficient of 0.50. The results of this study provide managerial implications that efforts to improve employee performance and job satisfaction can be done with the increase in compensation, teamwork, and organizational culture